1996
DOI: 10.1016/0300-483x(95)03173-d
|View full text |Cite
|
Sign up to set email alerts
|

Biliary excretion of biochemically active cyanobacteria (blue-green algae) hepatotoxins in fish

Abstract: Previous reports demonstrated that microcystin and related cyanobacteria polypeptides are rapidly cleared from plasma and accumulate in liver tissue. In the present study, we have used their ability to inhibit protein phosphatases to show that these cyanobacteria hepatotoxins are excreted into the bile of experimentally poisoned rainbow trout. At various times after oral administration of hepatotoxic Microcystis aeruginosa, bile samples were analysed for microcystin content by methanol extraction and protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 25 publications
5
42
1
1
Order By: Relevance
“…Compared with rainbow and goldfish, the depuration rate of MCs is much higher in the liver of silver carp. Fischer et al (2000) suggested that two factors may contribute to the decrease in extractable microcystin: one is biliary excretion of MCs or its metabolites (Sahin et al, 1996), the other is the slow covalent addition of MCs to the catalytic subunit of PP and other thiol containing cellular proteins (Hitzfeld et al, 1999) e.g., glutathione (Kondo et al, 1996), which may contribute to the progressive necrosis of hepatocytes. In the present study, although approximately 99% of accumulated MC-LReq.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with rainbow and goldfish, the depuration rate of MCs is much higher in the liver of silver carp. Fischer et al (2000) suggested that two factors may contribute to the decrease in extractable microcystin: one is biliary excretion of MCs or its metabolites (Sahin et al, 1996), the other is the slow covalent addition of MCs to the catalytic subunit of PP and other thiol containing cellular proteins (Hitzfeld et al, 1999) e.g., glutathione (Kondo et al, 1996), which may contribute to the progressive necrosis of hepatocytes. In the present study, although approximately 99% of accumulated MC-LReq.…”
Section: Discussionmentioning
confidence: 99%
“…The food safety of those fish is still a big problem. Some researches found some fishes could depurate microcystins accumulated in the liver through biliary excretion (Sahin et al, 1996) and some fishes can degradate microcystins (Xie et al, 2004). Expanded researches should be focusing on the effect of chronic microcystins exposure on different fishes and food safety warrantee.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that MCs are potent inhibitors of protein phosphatases 1 and 2A (MacKintosh et al, 1990;Toivola et al, 1994;Guzman et al, 2003) with liver as target organ. The high selectivity to liver is believed to be due to toxin uptake via bile acid carriers (Suchy, 1993;Sahin et al, 1996). Histopathological studies in both fish and mammals revealed serious lesions of the liver including rounding and separation of hepatocytes, disruption of hepatic cords, hepatocyte necrosis and degeneration, and severe intrahepatic hemorrhage leading to lethal hypolovemic shock or liver failure (Guzman and Solter, 2002;Li et al, 2003Li et al, , 2004Malbrouck et al, 2003;Handeland and Ostensvik, 2010).…”
Section: Introductionmentioning
confidence: 99%